The Effectiveness of Weight Training on Speed in Rock Climbing Athletes in the Speed World Record Category - Lutfiani, Devina; Irawan, Fajar Awang (Indonesian Journal of Physical Education and Sport Science, 2025)
Study Purpose. This study aims to determine the effectiveness of weight training on increasing the speed of rock climbing athletes in the Speed World Record category . Materials and methods. This study involved 10 Speed World Record category rock climbers from FPTI Semarang City. For one month, they followed a weight training program to increase muscle strength to support acceleration and climbing speed. Climbing time tests were conducted before (pretest) and after the training program (posttest). Data were analyzed using the T-Test to identify significant differences in average climbing time. Results. The results showed that the average climbing time decreased from 11.8610 seconds (pretest) to 10.6040 seconds (posttest), with a significant decrease of 1.257 seconds. The T-Test produced a significance value <0.001, indicating that this difference was very significant. Cohen's d> 0.8 indicates that the effect of weight training is very large on increasing athlete speed. Conclusion. This study found that weight training significantly improved the speed performance of Speed World Record category rock climbers. This decrease in time not only indicates an increase in movement efficiency but also represents a 10.6% reduction in climbing time, reflecting the strengthening of muscles and speed that support acceleration during climbing.